2020
DOI: 10.32598/irj.18.3.1046.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Acoustic Characteristics and Personality Dimensions in Patients With Dysphonia

Abstract: Objectives: Voice is influenced by personality. However, it is still questionable which acoustic features are influenced by personality traits. This study aimed to investigate the relationship between acoustic characteristics and personality dimensions. Methods: Thirty-three participants with dysphonia and 33 participants without dysphonia were recruited to take part in this cross-sectional study. Personality dimensions were evaluated by the revised NEO personality inventory, and acoustic characteristics by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…These findings are at odds with the previous research by Kasefy et al that showed openness had a large correlation with shimmer. It is assumed this difference might be due to the smaller sample size of this study done by Kasefy et al 27 Small to medium correlations between agreeableness with jitter and NHR and between conscientiousness with CPP were observed in participants without dysphonia. This finding is somewhat incongruent with the past study which found no correlation between agreeableness and jitter in participants without dysphonia.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…These findings are at odds with the previous research by Kasefy et al that showed openness had a large correlation with shimmer. It is assumed this difference might be due to the smaller sample size of this study done by Kasefy et al 27 Small to medium correlations between agreeableness with jitter and NHR and between conscientiousness with CPP were observed in participants without dysphonia. This finding is somewhat incongruent with the past study which found no correlation between agreeableness and jitter in participants without dysphonia.…”
Section: Discussionmentioning
confidence: 59%
“…This finding is somewhat incongruent with the past study which found no correlation between agreeableness and jitter in participants without dysphonia. As mentioned above, this difference might be attributed to the smaller sample size of the previous study 27 . Furthermore, a negative weak correlation between depression and jitter was found only in the dysphonia group.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations